Transformation of Migration Terminology: From ‘Illegal Migrant’ to ‘Irregular Migrant’ (English-Ukrainian Aspect) - Matvieieva, Svitlana; Matvieiev, Serhii (Review of European and Comparative Law, 2023)
This article deals with the study of the semantic transformation of terminological units for migration law. The question of standardization of national terminology, as well as inter- and intra-linguistic harmonization and unification of migration units is raised and substantiated. It is noted that changes in English terminology cause difficulties in national terminology due to, on the one hand, the need to find the most accurate and correct equivalent of the unit of the source language, and on the other – differences in the semantic volume of units of different languages. The article considers English terms for migrants: illegal migrant, irregular migrant, undocumented migrant. Analysis of international normative and advisory documents, as well as data from lexicographic sources of English and Ukrainian languages allow the authors to provide recommendations for the use of the Ukrainian equivalent to these terms – мігрант із неврегульованим статусом. At the same time, the authors note that the current Ukrainian legal documents operate on the term нелегальний мігрант, despite the long-standing recommendations of the Council of Europe and the UN to replace the term illegal migrant in national legislation with irregular migrant or undocumented migrant.